Differences in physiological responses between short- vs. long- graded laboratory tests in road cyclists - González-Haro, C. (The Journal of Strength and Conditioning Research, 2015)
This study aimed to determine the effect of a short-graded with respect to a long-graded protocol laboratory test on the physiological responses of road cyclists. Twenty well-trained road cyclists performed a short-graded and long-graded laboratory tests within 1 week of each other in a randomized and crossover study design. Blood lactate concentration ([La-]b), heart rate (HR), oxygen consumption (VO2), and carbon dioxide production (VCO2) were measured. Fat and carbohydrate oxidation rates (FATOxR and CHOOxR) were estimated at the end of each stage during the short-graded and the long-graded (10th minute: T2.10) and in the middle of long-graded (fifth minute: T2.5) protocol. Lactate threshold (LT) and individual anaerobic threshold (IAT) were calculated. For maximal intensities, duration and maxFATOxR were significantly higher in long-graded with respect to short-graded protocols. Peak power output (POPeak), HRPeak, [La-]bmax, VO2peak, and maxCHOOxR were significantly higher in short-graded with respect to long-graded protocols. At submaximal intensities, short-graded protocol provoked higher demands on glycolytic metabolism than long-graded protocol; no differences were illustrated for HR or VO2 between protocols. Crossover concept shifted to higher intensities in long-graded with respect to short-graded protocols due to the higher lipolytic response during the long-graded protocol. Both LT and IAT were reached at the same %VO2peak , although significantly higher PO in short-graded with respect to long-graded protocols was reached. The long-graded proved to be more specific than the short-graded protocol to assess the physiological responses of road cyclists based on relative PO (W/kg).